Identification of Novel HLA-A*24:02-Restricted Epitope Derived from a Homeobox Protein Expressed in Hematological Malignancies. - Maiko Matsushita; Yohei Otsuka; Naoya Tsutsumida; Chiaki Tanaka; Akane Uchiumi; Koji Ozawa; Takuma Suzuki; Daiju Ichikawa; Hiroyuki Aburatani; Shinichiro Okamoto; Yutaka Kawakami; Yutaka Hattori (PLoS ONE, 2016)
The homeobox protein, PEPP2 (RHOXF2), has been suggested as a cancer/testis (CT) antigen based on its expression pattern. However, the peptide epitope of PEPP2 that is recognized by cytotoxic T cells (CTLs) is unknown. In this study, we revealed that PEPP2 gene was highly expressed in myeloid leukemia cells and some other hematological malignancies. This gene was also expressed in leukemic stem-like cells. We next identified the first reported epitope peptide (PEPP2(271-279)). The CTLs induced by PEPP2(271-279) recognized PEPP2-positive target cells in an HLA-A*24:02-restricted manner. We also found that a demethylating agent, 5-aza-2'-deoxycytidine, could enhance PEPP2 expression in leukemia cells but not in blood mononuclear cells from healthy donors. The cytotoxic activity of anti-PEPP2 CTL against leukemic cells treated with 5-aza-2'-deoxycytidine was higher than that directed against untreated cells. These results suggest a clinical rationale that combined treatment with this novel antigen-specific immunotherapy together with demethylating agents might be effective in therapy-resistant myeloid leukemia patients.